Pengembangan Media Pembelajaran Ular Tangga untuk Materi Eksponen Kelas X SMA - Mohamad Halim Dwi Kusuma; Yudi Irawan; Annisa Yulianti; Ribka Dwi Y.; Silvie Adhe S.; Leonard Leonard (Journal of Instructional Development Research, 2020)
This research was done to develop a learning media with a snakes and ladders game. in an age where all humans must develop so as not to be crushed by the time that is rapidly advancing ahead of us as educators we must also be able to harmonize the times of what we have to do with the teaching process Educators must also begin to grow and develop because students increasingly have a level of boredom about something that is too serious when trying to achieve something, but that doesn’t mean today's, children don’t have a high seriousness but it's just that they only want a renewal of something, then the problem of the scourge of mathematics which is always growing creepy in the minds of the public is a big challenge for us as educators who focus on the world of mathematics. Therefore, we must develop and change the minds of the audience towards their fear of mathematics. This is why we will develop a learning medium for the process of delivering a mathematical material with and use snake ladder media. We will make learning mathematics will be fun because it will be delivered by doing a game, this intends to make it easier for us to deliver the material and help students who receive the material will eliminate the fear of thinking about mathematics, this is the first step how a student can absorb what we will convey. In this study we used the method with a model ADDIE (Analysis-Design-Development-Implementation-Evaluation). This media is proven to assist teachers in presenting the material and students are also more easily understand the material presented. Thus, media development using ladder snake game deserves to be used. All we've done so far turned out is the result we expected. The purpose of this development really works when we try it on several X classes, their opinion after they finish studying the material we give you the snake ladder media is very easy for us when trying to understand the material provided and is very fun for us so we don't feel bored when the material is in progress.